The assessment of post-covid-19 Manifestations in recovered patients and The factors associated with high symptom burden (Bangladesh Journal of Medicine, 2023)
Background: Persistent COVID-19 symptoms and post-COVID chronic diseases have received more attention rather than the infection itself. This study’s goal was to evaluate the health status of recovered COVID-19 patients and analyze the factors associated with a high burden of symptoms.Methods: This was acohort study among hospital-released and recovered COVID-19 patients after three to six months of infection. Data was collected through a structured interview and analyzed by IBM SPSS (version25).Results: Fatigue (74.2%) followed by anxiety (38.9%) and joints paint (34.7%) were the most common symptoms of post-COVID period. Among participants, 21.34% had low dietary adherence and 17.2% had high adherence. A statistically significant correlation of high symptoms burden with dietary adherence and age was observed. People with low dietary adherence are at risk of high symptom burden and chronic diseases (AOR: 3.56, 95%CI:1.46-8.69). Habit of smoking, Asthma, Hypothyroidism, Ischemic heart disease are significant predictor (P